Building Financial Inclusion: The Role of Rural Banks and Cooperatives as Motors of Micro and Medium Economic Growth - Moh. Idil Ghufron; Ariska Anggraini; Riskina Fauziyah; Holifah; Yayi Wulandari (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2024)
This study aims to examine the role of rural banks (BPR) and cooperatives in supporting the economic growth of the Micro, Small and Medium Enterprises (MSMEs) sector in Indonesia. The research method used is qualitative research with a descriptive approach. Data were collected through literature studies from various related literature. The results showed that MSMEs have an important role in the structure of the Indonesian economy, contributing more than 99% of GDP and absorbing most of the workforce. However, its existence also faces challenges and limitations, such as capital problems, production techniques, market share, management, and licensing. BPR and cooperatives have a strategic role in supporting the MSME economy. BPR provides funds distribution to MSMEs in the form of working capital loans, while cooperatives act as business entities consisting of individuals or legal entities with the principles of kinship and mutual assistance. Efforts to strengthen the MSME sector continue to be carried out by the government, the private sector, and the community. Collaboration between financial institutions, including rural banks and cooperatives, with Islamic economic principles has also been tested.